Isolation and characterization of a catalase-peroxidase gene from the pathogenic fungus, Penicillium marneffei - Pongpom P. (2014)
Penicillium marneffei is a facultative intracellular pathogen that causes common opportunistic infection in AIDS patients in Southeast Asian countries. The pathogen can usually survive and replicate inside the phagosome of macrophages, and is also found extracellularly in blood smears or host tissue. Surviving within the alveolar macrophage is a primary key to the success of P. marneffei invasion. However, the mechanism of survival under oxidative stress in this environment has not been elucidated. An antigenic catalase-peroxidase protein-encoding gene (cpeA) was isolated by antibody screening of a cDNA library derived from the yeast phase of P. marneffei. DNA sequence analysis of this gene revealed an open reading frame encoding a 748 amino acid polypeptide with a predicted molecular mass of 82.4 kDa. The deduced amino acid sequence was 45-69% identical to that of catalase-peroxidases from many bacteria and fungi. Potential iron regulated binding elements and conserved active sites for peroxidases were found in the peptide sequence. Southern blot analysis showed that the P. marneffei genome contained a single copy of the cpeA. This gene displayed a high level of expression, specifically being induced when the temperature was shifted to 37°C, the condition whereby the pathogenic yeast phase of P. marneffei is formed. The high expression of the cpeA mRNA transcripts at 37°C may contribute to the survival of this dimorphic fungus in host cells. © 2005 ISHAM.